Design, Development And Evaluation Of A Web Courseware With A Pedagogical Agent - Zalib, Mohd Feham Md. Ghalib @ Md. (2006)
This study examined the effects of a pedagogical agent (PA) with different levels of personalization in a web courseware on the learning of thematic materials. These effects were studied based on the Strategy Inventory in Language Learning (SILL). Two modes of an interactive multimedia web courseware on the theme of the holy city of AI-Quds were systematically designed and developed. While the first mode used a personalized version of the pedagogical agent (PPA), the second mode used a nonpersonalized PA (NPPA). The personalization elements include an integration of social cues, dialogue conversations, and indirect feedback. The courseware was developed based on Alessi and Trollip's (2001) Model of Design and Development of Multimedia Learning. The rationale of adopting pedagogical agents in a web learning environment is based on Vygotsky's social learning theory (1978) , communication theory (Reeves & Nass, 1996), cognitive multimedia learning theory (Mayer, 2001), and cognitive flexibility theory (Spiro et al., 1992). A 2 x 3 quasl-experimental factorial design was used in this study. The independent variables were the two modes of presentation (PPA and NPPA). The dependent variables were the learning gains and the program rating score. The moderator variable was the SILL score. 96 students studying the Arabic language at an advanced level at the International Islamic University Malaysia participated in the study. The students were divided into three groups using the PPA mode and four groups using the NPPA mode. Descriptive and inferential statistics were used to analyze the collected data. Two-way and One-way ANOVA procedures were used to examine the main and interaction effects between the independent variable and the dependent variables.